An Immersive Journey Through Early Electronic Works of… (un)usual suspects - Parra Cancino, Juan; An Immersive Journey Through Early Electronic Works of… (un)usual suspects Koetshuis Orpheus Instituut 26 February 2024 (2024)
Tape, Vinyl, and digital, multichannel fixed support pieces, presented in their original formats.
Listening sessions of Early Electronic Music
FRIS
0
Keywords: Music, Thought and Technology